Bank Restructuring and Resolution - Hoelscher, David S. (International Monetary Fund, 2006)
Systemic financial crises have become a common, albeit infrequent, feature of the global financial landscape. Since 1980, nearly every country has been affected by serious financial distress or systemic financial crises. Resolution of such crises requires a complex mix of macroeconomic and financial sector policies. One important element in the mix is the restructuring and resolution of problem banks. Considerable experience has been gained in this area in the past decade. This volume outlines the theoretical insights gained and the practical lessons learned. For more information on how to purchase this title, please visit http://www.palgrave.com/economics/imf/index.asp.